Validation of Residual Tied Ridging Insitu Rainwater Harvesting Labor Saving Technology in Semi-Arid Areas of Central Tanzania - Tanzania Agricultural Research Institute; International Institute of Tropical Agriculture; University of Dodoma (International Food Policy Research Institute, 2023)
This dataset presents the data used in the study that was undertaken in four villages which had tied ridges constructed on 2016/2017 cropping season. It involved the use of a split-plot design with two factors namely tillage methods (i.e. annual tied ridging (ATR), residual tied ridging (RTR) and conventional farmer practice, (CFP) and two improved maize varieties (one commercial maize variety commonly grown by participating farmers) and one promising drought tolerant maize (DT) variety released by CIMMYT (WEMA) and ICRISAT (NACO Mtama 1). These trials consisted of six treatments that were replicated three times at each site. All treatments were applied with 20kg P/ha of Diammonium Phosphate (DAP) fertilizer at planting and Urea (40 kg N/ha) will be applied as a topdressing. Biophysical and socio-economic data will be collected and analyzed. The study consists of two cereal based systems notably:1. Maize based cereal system and treatments 2. Sorghum based cereal system.